HEALTH PROMOTION, CARE AND SOCIAL AWARENESS AMONG HOMELESS PEOPLE: AN EXPERIENCE REPORT OF MEDICAL STUDENTS (CIPEEX, 2025)
Introduction: Academic activities that bring students closer to contexts of social vulnerability provide opportunities for health promotion in non-conventional settings and for development of empathy and caregiving skills. In Anápolis (GO), actions were carried out with the homeless population, offering food, clothing, and bathing facilities, as well as opportunities for dialogue, active listening, and emotional support. Objective: This report describes the experience of medical students from UniEVANGÉLICA in educational activities with people experiencing homelessness, aiming to promote health education, strengthen bonds, foster empathy and social responsibility, while also encouraging critical thinking and the humanized practice of care. Methods: The activities took place biweekly, on Fridays, with homeless the individuals. At each meeting, in addition to the distribution of meals and clothing, students performed blood pressure measurement and organized discussion circles on relevant topics such as the prevention of sexually transmitted infections (STIs), personal hygiene, alcohol and drug use, wound care, and self-care. These actions were designed to encourage the adoption of healthy habits, stimulate attention to one’s own health, and provide practical guidance, fostering interaction, dialogue, and mutual learning. Results: It was observed that, beyond interest in health guidance, participants especially valued moments of conversation and listening. Many shared difficult life experiences and expressed satisfaction upon receiving attention, care, and genuine interest from the students. The actions enabled not only the transmission of health information but also the creation of affective and trust-based bonds between volunteers and the assisted population. Conclusion: The experience provided UniEVANGÉLICA medical students with direct exposure to the reality of homelessness, fostering empathy, social responsibility, and commitment to health promotion. At the same time, it offered participants moments of care, listening, and learning, strengthening the students’ comprehensive and humanized education.
Keywords: Health education; Empathy; Homeless population